Implementation of The Wamanggu Market Retribution Management Policy as Regional Income in Merauke Regency - Paul Adryani Moento; Albertus Yoseph Maturan; David Laiyan; Erwin Nugraha Purnama (Journal of Public Administration and Government, 2022)
Policy implementation is the execution of a government work program that results from a consensus of stakeholders with the goal of improving community welfare. The goal of this research is to present an outline of the Wamanggu Market Retribution Management Policy as Regional Income in Merauke Regency. In order to collect study data, researchers interviewed 11 persons who served as informants. The descriptive approach was used to analyze the data. The author employs a qualitative method in this study, and the data analysis process consists of three stages: data reduction, data presentation, and conclusion drawing. According to the findings of the communication research, there existed information in the form of oral and written communication. In terms of resources, there is also the deployment of personnel to supervise punishment for the Wamanggu market. Furthermore, there is a pledge packed in a meeting with traders at the Wamanggu market, as well as the engagement of the fish quarantine and fisheries product security agency, which carries out cleaning activities.